1992
DOI: 10.1007/bf00233093
|View full text |Cite
|
Sign up to set email alerts
|

First evidence of somatic embryogenesis from needles of 1-year-old Picea abies plants

Abstract: Somatic embryogenesis was obtained from hypocotyls and cotyledons of one month old plantlets of Picea abies. Embryogenic yield was higher with expiants from somatic embryo-derived plantlets (80 %) than with plantlets issued from zygotic embryos (10 %). This report also describes production of embryogenic calli from needles of 14 month old somatic embryo-derived plants cultivated in greenhouse. The influence of the physiological status and genotype of the mother plant on somatic embryogenic potential is discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

1995
1995
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 15 publications
0
14
0
2
Order By: Relevance
“…Plants produced by means of somatic embryogenesis are very good donors of explants, because their tissues are physiologically younger than zygotic embryos. The potential for embryogenic tissue initiation by explants decreases with age (Ruaud 1993;Ruaud et al 1992;Harvength et al 2001). Ruaud et al (1992) used as sources of explants some needles of one-year-old somatic and zygotic seedlings of P. abies.…”
Section: Induction Of Embryogenic Tissuementioning
confidence: 99%
See 1 more Smart Citation
“…Plants produced by means of somatic embryogenesis are very good donors of explants, because their tissues are physiologically younger than zygotic embryos. The potential for embryogenic tissue initiation by explants decreases with age (Ruaud 1993;Ruaud et al 1992;Harvength et al 2001). Ruaud et al (1992) used as sources of explants some needles of one-year-old somatic and zygotic seedlings of P. abies.…”
Section: Induction Of Embryogenic Tissuementioning
confidence: 99%
“…The potential for embryogenic tissue initiation by explants decreases with age (Ruaud 1993;Ruaud et al 1992;Harvength et al 2001). Ruaud et al (1992) used as sources of explants some needles of one-year-old somatic and zygotic seedlings of P. abies. A higher frequency of embryogenic tissue initiation was achieved by those authors from the former type of explants (80%), while only 10% of needles of zygotic seedlings were able to regenerate embryogenic tissue.…”
Section: Induction Of Embryogenic Tissuementioning
confidence: 99%
“…For initiation of embryogenic tissue in spruce, researchers have used immature (Hakman et al 1985) and mature zygotic embryos (Gupta and Durzan 1986;von Arnold 1987;Adams et al 1994;Hazubska and Szczygie³ 2003) or cotyledons and hypocotyls of germinating zygotic or somatic embryos and needles (Lelu et al 1987;Lelu and Bornman 1990;Ruaud et al 1992;Ruaud 1993). Recently, Harvengt et al (2001) indicated that embryogenic callus can be initiated from needles of 3-year-old somatic seedlings.…”
Section: Embryogenic Callus Initiationmentioning
confidence: 99%
“…También se puede lograr embriogénesis a partir de elementos florales (Merkle y Battle, 2000;Toribio et al, 2000), pero en este caso hay que confirmar si se trata de embriogénesis somática o gamética. En algunas especies de coníferas se ha logrado la inducción de embriogénesis somática a partir de tejidos no embrionarios (Atree et al, 1990;Ruaud et al, 1992), pero las referencias sobre árboles adultos son todavía escasas, como la patente sobre Pinus pinaster, citada en Ramarosandratana et al (1999), y la inducción en ápices vegetativos de ár-boles de 20 años en Pinus radiata (Smith, 1999) y de 15 años en Pinus patula (Malabadi y van Staden, 2005).…”
Section: Las Fases De La Regeneración Por Embriogénesis Somática Induunclassified